SUMOylation, a multifaceted regulatory mechanism in the pancreatic beta cells. (July 2020) - Li, Na; Zhang, Shu; Xiong, Fei; Eizirik, Decio L.; Wang, Cong-Yi
Highlights: We summarize recent progress about how SUMOylation regulates beta cell function and viability. SUMOylation levels in beta cells are influenced by the cellular redox status. SUMOylation interplays with other PTMs (e.g., phosphorylation, ubiquitination and Neddylation) in beta cells SUMOylation can affect beta cell senescence probably by modifying senescence-related key molecules, such as NOTCH1 and p53. SUMOylation is a promising modulator in beta cell RNA processing. Abstract: SUMOylation is an evolutionarily conserved post-translational modification (PTM) that regulates protein subcellular localization, stability, conformation, transcription and enzymatic activity. Recent studies indicate that SUMOylation plays a key role in insulin gene expression, glucose metabolism and insulin exocytosis under physiological conditions in the pancreatic beta cells. Furthermore, SUMOylation is implicated in beta cell survival and recovery following exposure to oxidative stress, ER stress and inflammatory mediators under pathological situations. SUMOylation is closely regulated by the cellular redox status, and it collaborates with other PTMs such as phosphorylation, ubiquitination, and NEDDylation, to maintain beta cellular homeostasis. We hereby provide an update on recent findings regarding the role of SUMOylation in the regulation of pancreatic beta cell viability and function, and discuss its potential implication in beta cell senescence and RNA processing ( e.g ., pre-mRNA splicing and mRNA methylation). Through which we intend to provide novel insights into this fundamental biological process regarding both maintenance of beta cell viability and functionality, and beta cell dysfunction in diabetes mellitus.